Evaluation of Cost-Effectiveness and Patient Satisfaction of Topical, Topical Plus Systemic, and Topical Plus Laser Treatment in Patients with Acne Vulgaris High Level - Indra Ginting; Hassan Basri Mukhali; Robert Parulian Sinaga; Tiwanto Dakhi; Andrey Bayu Aji; Novi Supit; Singgar Ni Rudang; Syahniar Lubis; Mohd Ihsanuddin Bin Abas (Newinera Publisher, 2025)
Acne vulgaris is a prevalent dermatological condition that negatively affects quality of life and psychological well-being. Although topical, systemic, and laser therapies are commonly used, comparative evidence on their effectiveness, patient satisfaction, and cost-effectiveness in Southeast Asia remains limited. This prospective cohort study was conducted at Erha Clinic from April 2024 to March 2025. Ninety patients with acne vulgaris were evenly allocated into three treatment groups: topical monotherapy, topical plus systemic therapy, and topical plus laser therapy. Clinical effectiveness was assessed using lesion counts and the Investigator Global Acne (IGA) scale, patient satisfaction using the Visual Analogue Scale (VAS), and cost-effectiveness through total cost and cost per lesion reduction. Measurements were taken at baseline and at weeks 2, 4, 8, and 12. Data were analyzed using IBM SPSS version 22. All treatment modalities significantly reduced acne lesions and improved IGA scores and patient satisfaction. Topical plus laser therapy achieved the fastest and greatest lesion reduction and highest satisfaction but incurred the highest cost. Topical monotherapy demonstrated comparable long-term clinical outcomes with the lowest cost per lesion reduced, indicating superior cost-effectiveness. All treatments were clinically effective; however, topical monotherapy was the most cost-effective option, while topical plus laser offered faster results at higher cost. Treatment selection should balance clinical benefits and economic considerations, particularly in resource-limited Southeast Asian settings.